Colchicine for gout - M. S. Eliseev; M. N. Chikina; A. M. Novikova (Медицинский совет, 2021)
Colchicine is a drug that has been known for several millennia, since the days of Ancient Egypt, but has been successfully used to treat gout to this day. The action of colchicine is based on microtubule damage, mitosis suppression, as well as the ability to inhibit the activation of NLRP3 inflammasoma by monosodium urate crystals and block the release of interleu-kina (IL)-1p - key cytokine in the development of gout inflammation. However, the mechanism of action of colchicine is still not fully understood.Colchicine should be considered as the optimal drug not only for relieving an acute attack of arthritis in gout, but also as the best method for preventing attacks of gouty arthritis when choosing urate-lowering therapy. Recent studies have confirmed the good efficacy and safety profile of the drug when used correctly in patients with gout. Currently, it is recommended to use low doses of the drug (1-1.5 mg per day to relieve an acute attack of arthritis and 0.5-1.0 mg to prevent attacks when initiating uratelowering therapy). At the same time, according to the results of recent studies on the effectiveness, low doses are not inferior to high doses, but when low doses are used, the frequency of undesirable effects is much less. Unlike non-steroidal anti-inflammatory drugs and glucocorticoids, the drug does not have a negative effect on the cardiovascular system and can be used in patients with diabetes mellitus. This allows the drug to be used for a long time, which is especially important, since it is recommended to prevent arthritis attacks for at least 6 months from the start of taking urate-lowering drugs. This avoids the exacerbation of arthritis in most patients and significantly reduces their frequency. In addition, in the light of the accumulating data on the effect of the drug on the cardiovascular system of the drug, in conjunction with the high safety profile, other points of application should be considered where both anti-inflammatory and cardioprotective properties of colchicine can be used.